Resuscitative efficacy of hemoglobin vesicles for severe postpartum hemorrhage in pregnant rabbits - Hiroki Ishibashi (Nature Portfolio, 2021)
Abstract We aimed to investigate the resuscitative efficacy of hemoglobin vesicles (HbVs) as a red blood cell (RBC) substitute for the initial treatment of severe postpartum hemorrhage (PPH). Twenty-five pregnant rabbits underwent cesarean section; uncontrolled hemorrhage was induced by transecting the right uterine artery to establish a severe PPH model. During the first 30 min, all rabbits were administered 6% hydroxyethyl starch (HES) of an equivalent volume to the hemorrhage every 5 min. Thereafter, they received any of the following three isovolemic fluids for resuscitation every 5 min: RBCs with platelet-poor plasma (RBC/PPP) (n = 8), 6% HES (n = 7), or HbVs with 25% human serum albumin (n = 10). After surgical hemostasis at 60 min, survival was monitored until 12 h. No rabbits receiving only HES infusion survived beyond 6 h, whereas all rabbits receiving RBC/PPP transfusion survived. The rabbits receiving HbV infusion showed significantly higher mean arterial pressure and hemoglobin levels than the HES-receiving rabbits, and 8 of 10 rabbits survived for 6 h. The HbV group showed significantly higher survival than the HES group but worse survival than the RBC/PPP group. In conclusion, HbV infusion for severe PPH effectively prevents lethal hemorrhagic shock in a pregnant rabbit model.